UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PEGAGAN (Centella asiatica (L.) Urban) TERHADAP BAKTERIStaphylococcus epidermidis - Miki Rofi’atun Masriah; Supriyanto; Estuningtyas Ayu Hapsari (Universitas An Nuur, 2024)
Background: Acne is a skin problems characterized by the appearance of papules, pustules, blackheads, and nodules. Acne can be exacerbated by the bacteria Staphylococcus epidermidis which infects inflamed skin tissue. Antibiotic can be used to treat infections, but they can cause side effects. Therefore it is necessary to do alternative medicine using natural ingredients. Pegagan (Centella asiatica (L.) Urban) leaves contain active compouds such as alkaloids, triterpenoids, saponins, flavonoids, and tannins which are antibacterial because they can damage bacterial cell walls. Purpose: The aim of this research was to determine the antibacterial activity of pegagan (Centella asiatica (L.) Urban) leaf extract against Staphylococcus epidermidis bacteria. Method: This type of research is an experimental study with the disc diffusion method. Pegagan (Centella asiatica (L.) Urban) leaves were extracted by maceration method using 70% ethanol as solvent. Pegagan (Centella asiatica (L.) Urban) leaves extract at made contrations of 60%, 80%, 100%. Results: The results showed that pegagan (Centella asiatica (L.) Urban) leaf extract with concentrations of 60%, 80% and 100% had an average zone of inhibition of 18,39 mm, 21,24 mm and 22,61 mm. Conclusion: Pegagan (Centella asiatica (L.) Urban) leaf extract has antibacterial activity against Staphylococcus epidermidis bacteria